2011
DOI: 10.1111/j.1439-0531.2011.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Immunocastration Vaccine Composed of Gonadotrophin‐releasing Hormone Conjugated with Salmonella typhimurium Flagellin in Rats

Abstract: Immunocastration is an alternative method to replace surgical castration that is commonly performed in domestic and pet animals. In this study, a new immunocastration vaccine was developed, and its efficacy was evaluated in male rats. Six tandem copies of gonadotrophin-releasing hormone (GnRH) peptide were genetically fused to Salmonella typhimurium flagellin fljB (STF2) that is a ligand of toll-like receptor 5 (TLR5). The recombinant STF2-GnRH protein expressed in Escherichia coli was used as the immunocastra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…ab8491; Abcam, UK) and anti-flagellin polyclonal antibodies (cat no. ab93713, Abcam), as previously described [13][14][15][16].…”
Section: Recombinant Gnrh-i Gnrh-ii and Gnrh-i+ii Complex Proteinsmentioning
confidence: 99%
“…ab8491; Abcam, UK) and anti-flagellin polyclonal antibodies (cat no. ab93713, Abcam), as previously described [13][14][15][16].…”
Section: Recombinant Gnrh-i Gnrh-ii and Gnrh-i+ii Complex Proteinsmentioning
confidence: 99%
“…Additionally, there were no obvious pathologic changes in the histology of the testis or epididymis between the peptide group and the PBS group. Previous studies have reported an apparent decrease in testis and epididymal weights, as well as obvious pathologic changes in the seminiferous tubules, of immunization animals . However, other studies have shown no pathological changes in the testis and epididymis .…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported an apparent decrease in testis and epididymal weights, as well as obvious pathologic changes in the seminiferous tubules, of immunization animals. 3,[27][28][29] However, other studies have shown no pathological changes in the testis and epididymis. 1,15,16,30 Our study was consistent with the latter.…”
Section: Analysis Of Male Reproductive Organsmentioning
confidence: 91%
“…Similar immune responses were found when using polysine dendrimers or carbohydrate (glucose) as a branching core in vaccine construct [90]. Song et al carried out a study using a recombinant protein expressing LHRH with a heatshock protein to immunise BALB/c mice which led to reduced follicular development in their reproductive organs [94]. This recombinant vaccine construct also showed an inhibitory effect on mammary tumour cells [94].…”
Section: Carbohydrate Corementioning
confidence: 68%
“…Song et al carried out a study using a recombinant protein expressing LHRH with a heatshock protein to immunise BALB/c mice which led to reduced follicular development in their reproductive organs [94]. This recombinant vaccine construct also showed an inhibitory effect on mammary tumour cells [94]. Immunisation of ICR male and female mice with a genetic vaccine encoding LHRH with five T helper epitopes in one sequence, effectively reduced testosterone to 75% lower than the baseline and impaired testicular function in male mice and suppressed folliculogenesis in female mice, thus inhibiting fertility in both mouse groups [100].…”
Section: Carbohydrate Corementioning
confidence: 99%